Perancangan dan Implementasi Sistem Informasi Reservasi Tamu di SEI Hotel Menggunakan Framework CodeIgniter - Sihombing, Agustria Sales; Ihsanuddin; Mukhtar (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2024)
The guest reservation information system is one of the data processing activities at SEI Hotel, designed to obtain more structured and accessible information about guest reservation reports. In this research, the author focuses on the design of a guest reservation information system at SEI Hotel using the CodeIgniter framework, with HTML, PHP, CSS, JSON, AJAX, and MySQL as database support. The objective of this research is to analyze and design the guest reservation information system at SEI Hotel using the CodeIgniter framework and the aforementioned programming languages and tools. Data collection for this report was conducted using two methods: literature review, which included books and other academic sources, and field studies through interviews and direct observation of relevant objects. The guest reservation information system was operated by an administrative staff member in the finance department to record and input guest reservation data. Based on the results of the research, it can be concluded that the guest reservation information system at SEI Hotel follows the proper procedures by utilizing the CodeIgniter framework, with HTML, PHP, CSS, JSON, AJAX, and MySQL as database support.